2005
DOI: 10.1002/anie.200500784
|View full text |Cite
|
Sign up to set email alerts
|

Achiral Ligands Dramatically Enhance Rate and Enantioselectivity in the Rh/Phosphoramidite‐Catalyzed Hydrogenation of α,β‐Disubstituted Unsaturated Acids

Abstract: In 2000, three research groups demonstrated that the widely held view that chiral bidentate ligands are necessary to achieve high enantioselectivity in rhodium-catalyzed hydrogenations needs revision. Monodentate phosphonites, [1a] phosphites [1b] and phosphoramidites [1c] proved to be highly versatile ligands for this important transformation and afforded excellent enantioselectivities for a broad range of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(47 citation statements)
references
References 34 publications
0
46
0
1
Order By: Relevance
“…Heterocombinations of monodentate chiral phosphonites with achiral phosphites or phosphanes [33] and chiral phosphoramidites with achiral phosphanes [34] improved the conversion and enantioselectivity in the Rh-catalyzed hydrogenation reactions compared to the systems formed by homocombination of two chiral ligands. This strategy has been further extended.…”
Section: Combination Of Phosphanesmentioning
confidence: 98%
“…Heterocombinations of monodentate chiral phosphonites with achiral phosphites or phosphanes [33] and chiral phosphoramidites with achiral phosphanes [34] improved the conversion and enantioselectivity in the Rh-catalyzed hydrogenation reactions compared to the systems formed by homocombination of two chiral ligands. This strategy has been further extended.…”
Section: Combination Of Phosphanesmentioning
confidence: 98%
“…It is estimated that large volumes of this intermediate will be required in the future but the best ee reported so far for production of this intermediate is 95 % as shown in Figure 1.8. [9] A study by Hoen et al [10] in collaboration with scientists from DSM indicates that the MONOPHOS derivative (D) together with added triphenylphosphine improves both the rate of reaction and enantioselectivity and may offer an improved system for this important target as can be seen from the analogous reaction reported by these authors and shown in Figure 1.9. The drug candidate OPC-51803 is the first nonpeptide vasopressin V 2 -receptorselective agonist that is in phase II clinical trials and the best chiral reduction to the intermediate acid (E) was with ruthenium acetate-[(S)-H8-BINAP] that gave a 77 % ee [11] (Figure 1.10).…”
Section: A-alkyl Substituted Acidsmentioning
confidence: 95%
“…[29] NMR studies have revealed that homocombinations, e.g., (P a ) 2 M; see Equation (1), are present in the mixture and these species can lower the overall catalytic performance of the system. [30] P a + P b + M Ǟ (P a ) 2 M + P a P b M + (P b ) 2 M…”
Section: Application Of Polymer-supported Ligands In the Heterocombinmentioning
confidence: 99%